Pedagogical Interventions for Enhancing Students’ Mathematical Literacy: A Systematic Literature Review - Udil, Patrisius Afrisno; Dasari, Dadan; Nurlaelah, Elah (Pedagogika, 2025)
This review examines pedagogical interventions to enhance mathematical literacy in Indonesia. It analyses research trends, objectives, types and characteristics of interventions, and the teachers’ roles. Thirty articles were selected using PRISMA protocol. The review identifies research trends across several aspects. Six intervention types and six teacher roles were identified. Each plays a key role in supporting students’ mathematical literacy. Future research directions are also discussed.